A Geophysical investigation and geological interpretation of part of the diamondiferous gravels on the farm Grasfontein (356 JP), west of Barkerville - upetd@up.ac.za (University of Pretoria, 2013)
Dissertation (MSc (Geology))--University of Pretoria, 2007.